POTENCIAL EMPRENDEDOR DE LOS ESTUDIANTES DE LA ESPECIALIDAD DE NEGOCIOS INTERNACIONALES DE LA UNMSM - Pérez Palacios, Emma Emilia (2009)
The present investigation has as an aim the study of the enterprising attitude from the point of view of the values, cradle in the theory of Schwartz, that maintains that the values influence in the decision of the people when forming a company. It is an investigation of descriptive type - explanatory applied to the students of the specialty of International Businesses of the Universidad Nacional Mayor de San Marcos. The methodology used for the treatment of the data is of descriptive and inferencial character. The result of the investigation sample that exists a direct relation between the enterprising capacity and the values of the students, as well, is characterized because they enjoy and so they do, have independence in the thought, choose his own goals; having familiar businessmen influences significantly in its decision to form companies, reason why we can conclude that they own enterprising characteristics that need to be reinforced so that the future they become success businessmen.